2000
DOI: 10.1093/nar/28.18.3625
|View full text |Cite
|
Sign up to set email alerts
|

2'-Deoxy-2'-fluoro-beta-D-arabinonucleosides and oligonucleotides (2'F-ANA): synthesis and physicochemical studies

Abstract: Recently, hybrids of RNA and D-arabinonucleic acids (ANA) as well as the 2'-deoxy-2'-fluoro-D-arabinonucleic acid analog (2'F-ANA) were shown to be substrates of RNase H. This enzyme is believed to be involved in the primary mechanism by which antisense oligonucleotides cause a reduction in target RNA levels in vivo. To gain a better understanding of the properties of arabinose based oligonucleotides, we have prepared a series of 2'F-ANA sequences of homopolymeric (A and T) and mixed base composition (A, T, G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
178
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 38 publications
14
178
2
Order By: Relevance
“…The synthesis of the 1-[2-deoxy-2-fluoro-5-O-(4,4′-dimethoxytrityl)-3-O-( -cyanoethyl-N,N-diisopropylphosphoramidite)--D-arabinofuranosyl] thymine monomer was previously described (13)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the 1-[2-deoxy-2-fluoro-5-O-(4,4′-dimethoxytrityl)-3-O-( -cyanoethyl-N,N-diisopropylphosphoramidite)--D-arabinofuranosyl] thymine monomer was previously described (13)…”
Section: Methodsmentioning
confidence: 99%
“…CD-spectra of DNA/RNA, FANA/RNA, and ANA/RNA duplexes in solution, although displaying close similarity, show distinct positive bands near 270 nm (13). Both X-ray crystallography and NMR solution studies indicated the O4′-endo (East (18)) conformation as preferred by FANA sugars (19,20).…”
mentioning
confidence: 95%
“…In the crystallographic model, the carbonyl group of the amide moiety faces the minor groove, and the methyl substituent is directed away from the duplex ( Figure 5). The structure allows no firm conclusions regarding a potential role of the solvent in the stability increases as a result of the amide modification because the current model includes only a limited number of water molecules (17). It is possible that an R-configuration of the methyl substituent (modification III) would lead to closer contacts between the methyl group and the sugar moiety of the 5′-T ( Figure 5).…”
Section: ′-Cgcaaaaaaaaaacgc-3′ (Complementary To B)mentioning
confidence: 97%
“…Some of the most prominent examples are 2 0 -fluoro (2 0 -F), 107,108 2 0 -O-methyl (2 0 -OMe), 109 2 0 -methoxyethyl (2 0 -MOE), 110,111 2 0 -fluoroarabino (2 0 -FANA), 112 locked nucleic acid (LNA), 113,114 unlocked nucleic acid (UNA), 115,116 cyclohexenyl (CeNA) nucleic acid, 117,118 peptide nucleic acid (PNA), 119 phosphoramidate morpholino (PMO) 120 etc. Although many of the modified nucleotides have been successfully utilized in various nucleic acid-based therapeutic technologies, their relatively poor or no enzymatic recognition properties often pose a major challenge toward the development of biostable aptamers.…”
Section: Chemically Modified Aptamer-oligonucleotide Chimeramentioning
confidence: 99%